2014
DOI: 10.1371/journal.pone.0087474
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 1 Receptor Is a Prognostic Factor in Classical Hodgkin Lymphoma

Abstract: The interaction between the tumor cells in classical Hodgkin lymphoma (cHL) and the microenvironment includes aberrant activity of receptor tyrosine kinases. In this study we evaluated the expression, functionality and prognostic significance of Insulin-like growth factor-1 receptor (IGF-1R) in cHL. IGF-1R was overexpressed in 55% (44/80) of cHL patients. Phosphorylated IGF-1R was detectable in a minority of the IGF-1R positive tumor cells. The overall survival (OS, 98%) and 5-year progression-free survival (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 42 publications
4
36
0
Order By: Relevance
“…Furthermore, using specific markers (CD3, CD15, CD20, CD68), we identify IGF-I in specific cells of the microenvironment in cHL. Additionally, we confirm the presence of the IGF-1R in cHL cells as recently described (Liang et al 2014) by immunohistochemistry on a histopathological tissue array.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…Furthermore, using specific markers (CD3, CD15, CD20, CD68), we identify IGF-I in specific cells of the microenvironment in cHL. Additionally, we confirm the presence of the IGF-1R in cHL cells as recently described (Liang et al 2014) by immunohistochemistry on a histopathological tissue array.…”
Section: Introductionsupporting
confidence: 84%
“…So far, IGF-I mRNA and peptide have been found to be produced by human peripheral lymphocytes only in low amounts (Arkins et al 1993;Kelley and Arkins 1994) or after mitogen stimulation (Nyman and Pekonen 1993). Nevertheless, most recently, IGF-I has been shown to stimulate the in vitro tumour growth of Hodgkin cell lines via the IGF-1R, which has been localised in cHL tumour cells, whereas the ligand has been detected in the cell culture supernatant (Liang et al 2014) but remains to be localised. Thus, in the present study, we aimed at localising the ligand IGF-I in HRS cells of cHL, in the LP cells of NLPHL and in the microenvironment, which, as described above, is essential for the pathogenesis and maintenance of tumour cells and which in HL only constitute a minority of the tumour mass (Steidl et al 2011).…”
Section: Fig 5 Igf-i In Cd68+mentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, about 56% (22 of 39) of the specimens were found to be expressing IGF-1R, in line with the 55% expression rate reported by Liang et al However, in the case of HL, the expression of IGF-1R with regard to inhibitory options is somewhat arguable. Liang et al reported that IGF-1R is strongly expressed in mitotic cHL cells and inhibition of IGF-1R decreases proliferation and induces cell-cycle arrest in cell lines, but in clinical correlation analysis the expression of IGF-1R was found to be related with better prognosis (17). Koh et al recently reported a much lower expression of IGF-1R (about 14%) in HRS cells and found a similar prognostic value as reported by Liang et al (18).…”
Section: Discussionmentioning
confidence: 76%